Penerapan Sistem Metode Analitical hierarcy proces (AHP) Untuk Menilai Kinerja Guru Terbaik Atau Produktif Pada SDIT Greenvile Bekasi Jawa Barat - Lenny Lenny Oktavianingsih; ragil wijianto; Hidayat Muhammad Nur; Sutrisno Sutrisno (Informatics and Computer Engineering Journal, 2022)
One of the efforts of higher education institutions to ensure the quality of graduates and the teaching and learning process is to improve the quality of teacher performance in the teaching and learning process. The quality of educational institutions is determined by a minimum of three factors, namely students, teachers and teaching and learning facilities, these three factors are interrelated and mutually support each other in creating a good learning process. This study aims to build a decision support system to facilitate the assessment of the best and productive teacher performance in learning by using the Analytical Hierarchy Process (AHP) method. For the object of my research, I used teachers and school principals by distributing questionnaires for questions about learning in the classroom and the scope of the school that served as a tool for educational institutions in assessing the best teachers. In order for the purpose of this decision support system to be successful, research and observation are carried out as objects in the preparation. Keywords : Best Teacher Performance Decision Support System With Using the Analytical Hierarchy Process (AHP) method.